Cardiac Surgery : Operations on the Heart and Great Vessels in Adults and Children - Ziemer, Gerhard; Haverich, Axel (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This text describes and illustrates with some 700 detailed anatomic and surgical drawings the whole spectrum of surgical procedures employed to treat acquired and congenital diseases of the heart and great vessels in adults and children. A rather traditional chapter on history of cardiac surgery precedes chapters dedicated to quality improvement, followed by ICU management in adult and pediatric cardiac surgery, and techniques of extracorporeal circulation in both age groups. Further special topics are cardiovascular tissue engineering, minimally invasive cardiac surgery, endovascular treatment of aortic diseases, and cardiac assist devices, including total artificial heart. Written by 71 internationally recognized experts from 40 cardiac units in Central Europe and North America, this book will be invaluable not only for both novice and experienced surgeons, but also for all physicians, nurses, and technicians caring for patients with heart disease of any type, at any age.
Keywords: Medicine.; Critical care medicine.; Cardiology.; Surgery.; elektronické knihy; electronic books